Human Resource-Based Conflict Management for Enhancing Team Harmony in Educational Institutions - Lamminar Hutabarat (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
Conflict is an unavoidable phenomenon in organizations, including educational institutions. Interactions among individuals with diverse backgrounds and interests often generate tension that can disrupt the effectiveness of teamwork. This study aims to analyze the forms of conflict that occur, examine the human resource management approaches used to resolve them, and evaluate the effectiveness of these approaches in creating team harmony. A qualitative approach with a case study method was applied at an educational institution in Medan City. Data were collected through in-depth interviews, observation, and documentation. The findings reveal that conflicts generally stem from ineffective communication, unequal workload distribution, and differing perceptions of management policies. The human resource strategies applied included internal mediation, communication training, and efforts to strengthen a collaboration-oriented organizational culture. These approaches were found to be effective in reducing conflict and improving interpersonal relationships within the team. The study concludes that human resource based conflict management plays a crucial role in fostering harmonious and productive teamwork in educational environments, and can serve as a model for other institutions facing similar challenges.